PENGARUH APLIKASI POC KEONG MAS DAN GIBERELIN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI RAWIT (Capsicum frutescens L.) - Muhammad Zaid; Ernita (UIR Press, 2024)
This study aimed to assess the interaction and primary impact of varying concentrations of Golden Snail Liquid Fertilizer and Gibberellins on the growth and yield of Cayenne Pepper Plants (Capsicum frutescens L.). Conducted at the experimental farm of the Faculty of Agriculture at the Islamic University of Riau from February to June 2021, the research employed a 4 x 4 factorial design within a completely randomized framework, incorporating three replications. The first factor involved four levels of Golden Snail Liquid Fertilizer concentration: 0, 150, 300, and 450 ml per liter of water. The second factor examined four levels of Gibberellins concentration: 0, 20, 40, and 60 ppm. The parameters measured included plant height, flowering age, harvesting age, number of primary branches, fruit weight, and remaining fruit count. Statistical analysis of the research data was performed, followed by the 5% BNJ test. The findings indicated that the interaction between the concentrations of Golden Snail Liquid Fertilizer and Gibberellins significantly influenced all parameters measured, except for the number of primary branches. The optimal treatment was identified as a combination of 450 ml of Golden Snail Liquid Fertilizer per liter of water and 60 ppm of Gibberellins. Additionally, the concentration of Golden Snail Liquid Fertilizer had a significant primary effect on all observed parameters, with the most effective treatment being 450 ml per liter of water. Gibberellins also demonstrated a significant primary effect across all parameters, with the best concentration set at 60 ppm.